2022
DOI: 10.1371/journal.pone.0264556
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis patients have an altered gut mycobiome and increased fungal to bacterial richness

Abstract: Trillions of microbes such as bacteria, fungi, and viruses exist in the healthy human gut microbiome. Although gut bacterial dysbiosis has been extensively studied in multiple sclerosis (MS), the significance of the fungal microbiome (mycobiome) is an understudied and neglected part of the intestinal microbiome in MS. The aim of this study was to characterize the gut mycobiome of patients with relapsing-remitting multiple sclerosis (RRMS), compare it to healthy controls, and examine its association with change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
0
10
1
Order By: Relevance
“…Strikingly, both the analyses in pwMS exhibit a much higher rate of food-associated strains shown to survive passage through the human gut, in particular S. cerevisiae , that here represents 6.5% of the total isolates in MS, compared to a known frequency of less than 2% in HD ( 29 ), and S. delbrueckii , another food-borne yeast ( 47 49 ). Other recent studies ( 13 , 50 ) have shown alterations in the gut mycobiota of NEDA pwMS, but it is not yet clear if further alterations exist during the active phase of the disease.…”
Section: Discussionmentioning
confidence: 93%
“…Strikingly, both the analyses in pwMS exhibit a much higher rate of food-associated strains shown to survive passage through the human gut, in particular S. cerevisiae , that here represents 6.5% of the total isolates in MS, compared to a known frequency of less than 2% in HD ( 29 ), and S. delbrueckii , another food-borne yeast ( 47 49 ). Other recent studies ( 13 , 50 ) have shown alterations in the gut mycobiota of NEDA pwMS, but it is not yet clear if further alterations exist during the active phase of the disease.…”
Section: Discussionmentioning
confidence: 93%
“…Limitations of our study include lack of fecal and plasma metabolomics to directly measure potential differences in bacterial metabolites (especially butyrate, propionate, and urolithin) in CA and CNA patients. Gut mycobiome data would also have been helpful in getting the full picture of gut microbiota in MS, as a recent study found gut mycobiome altered in patients with MS [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…calcoaceticus both increased (induced proinflammatory responses), but Parabacteroides distasonis was reduced (stimulated anti-inflammatory IL-10-expressing) [99]. In addition, the abundance of Bacteroidetes, Lachnospiraceae, Rikenellaceae, Eisenbergiella, Escherichia-Shigella, F. prausnitzii, and Flavobacterium increased in patients with MS, whereas Firmicutes, Ruminococcaceae, Bacteroides, Bifidobacterium, Clostridium, L. salivarius, L. iners, L. ruminis, Megamonas, Odoribacter, Parabacteroides, and Prevotella decreased [99,[114][115][116][117][118][119][120][121][122][123][124][125][126][127][128] (Fig. 4).…”
Section: Multiple Sclerosismentioning
confidence: 99%